Integration of an interactive program in learning arabic language for non-native speakers via virtual tutor - Ahmed Mahmoud, Ahmed Ragheb; Muhammad Sabri Sahrir; Rahmah Ahmad H. Osman (Penerbit UKM, 2013)
This research presents the integration process of an interactive program specifically dedicated in teaching Arabic language to the non-native speakers. This program is established based on the complete awareness of the language contents and its four levels of language study (phonological, morphological, syntactical and semantic) with distinct focus on prominent foundations and theories concerned with academic accomplishment as derived from the e-learning data system. The research is established on textual and phonological database involving vocabulary comprehension and its manners of pronunciation and inferring to the most highly expected errors from the non-native speakers of Arabic. More than 120 users participated in the process, under the supervision of a specialized teamwork between the administrative, linguistic, educational and engineering departments. The tentative results statistically reflect the program‟s efficiency and its distinctive role in prompting the academic process and the increase in the cognitive outcome among the students who are assigned as the experimental sample group in comparison to the results of the realizable control sample from similar conventional education. This program garners practical and academic features ensuring more worth in studying it compared to other e-learning programs. In essence, Virtual Tutor does not only embody theoretical foundations which are supported with modern methodological designs, but it also simultaneously ensures efficient participatory role of the users.